Moral development in preschool children according to Kohlberg’s stages: A revised analysis from the perspective of Positive Psychotherapy - Elmedina Cesco (The Global Psychotherapist)
This study investigates the moral development of preschool children aged 3 to 6 in Kosovo, framed within Kohlberg’s theory of moral reasoning and principles of Positive Psychotherapy. The study measured moral reasoning levels and altruistic behaviors using the Early Development Instrument (EDI), which focused on social competence and emotional maturity. Results confirm that moral development follows the sequential stages outlined by Kohlberg, with cultural factors influencing specific moral expressions. Gender analysis revealed that girls exhibit higher altruistic behaviors than boys, aligning with existing literature. The findings highlight the critical role of pro-social parental modeling and culturally sensitive positive reinforcement in fostering moral and altruistic behaviors. This research underscores the importance of integrating cultural values and strengths-based approaches to support moral development in early childhood.